KONSEP ULAMA DALAM AL-QUR'AN DAN IMPLIKASINYA PADA WACANA KEPENDIDIKAN ISLAM - Kasuwi Saiban (STAI Ma'had Aly Al-Hikam Malang, 2012)
Ulama' are Prophet heirs, because of characteristic, personality, duty and ability they owned so that they are respected. And in Muslim society,